Women's Empowerment In Morocco: The Writing of The Muhammadi Mushaf By Morocco Women In The Eradication Of Illiteracy Program - Adim, Fauzan; Larhzizer, Fouad (LP2M IAIN kUDUS, 2024)
This article aims to reveal the Moroccan Government's efforts in empowering women, by involving them in real terms in the Literacy Eradication Program in mosques. This research is a qualitative research, with data collection techniques through interviews with several people related to the Literacy Eradication Program in Morocco and library data. By using descriptive analysis methods and the concept of women's empowerment as a tool for reading data, this article finds that the Moroccan government's efforts to empower women through the Ministry of Endowments in the Literacy Eradication Program in Mosques are carried out by involving women as teachers and participants. It is recorded that more than seven thousand teachers and instructors, program coordinators and education advisors from among women are actively involved in efforts to eradicate illiteracy in Morocco. In addition to being expected to develop social, economic and educational status, as well as improve the standard of living of individual program participants and also the community, this program concretely produced a mushaf written jointly by 75 thousand female program participants, which was then published under the name Al-Mushaf al-Mohammadi min Naskh an-Nisa` al-Mustafidat min Barnamij Muharabah al-Ummiyah fi al-Masajid bi Riwayah Warsy `an Nafi'.AbstrakArtikel ini bertujuan mengungkap upaya Pemerintah Maroko dalam pemberdayaan perempuan, dengan melibatkan mereka secara riil pada Program Pemberantasan Buta Huruf di masjid. Penelitian ini merupakan penelitian kualitatif, dengan teknik pengumpulan data melalui wawancara dengan beberapa orang yang berkaitan dengan Program Pemberantasan Buta Huruf di Maroko dan data kepustakaan. Dengan menggunakan metode deskriptif analisis dan konsep pemberdayaan perempuan sebagai alat membaca data, artikel ini menemukan bahwa upaya pemberdayaan perempuan pemerintah Maroko melalui Kementerian Wakaf dalam Program Pemberantasan Buta Huruf di Masjid, dilakukan dengan melibatkan perempuan sebagai pengajar dan peserta. Tercatat lebih dari tujuh ribu guru dan pengajar, koordinator program serta penasehat pendidikan dari kalangan perempuan terlibat aktif dalam upaya pemberantasan buta huruf di Maroko. Selain diharapkan dapat mengembangkan status sosial, ekonomi dan pendidikan, serta meningkatkan taraf hidup individu peserta program dan juga masyarakat, secara konkret program ini menghasilkan mushaf yang ditulis secara bersama-sama oleh 75 ribu perempuan peserta program, yang kemudian diterbitkan dengan nama Al-Mushaf al-Mohammadi min Naskh an-Nisa` al-Mustafidat min Barnamij Muharabah al-Ummiyah fi al-Masajid bi Riwayah Warsy `an Nafi’.